Performance Analysis of Reactive Routing Protocol on VANET with Wormhole Attack Schemeaper - Ratnasih Ratnasih; Doan Perdana; Triani Wulandari; M. Irfan Pratama (JURNAL INFOTEL, 2018)
Entering the information era, the current needs of the global community is increasing very rapidly. Vehicular Ad-hoc Networks (VANET) has drawn significant attention from both industry and academia as an important development of vehicular communication technology. VANET is one of open network and communication media without security mechanism. There are many kinds of security threat that can interrupt data communication in VANET. Wormhole attacks as one of security threat can be a good challenge in VANET security research. In this paper, we evaluate the performance of the reactive routing protocol on VANET with wormhole attack scheme. The project is simulated using NS-3 in Ubuntu platform with performance analysis of routing protocol by changing initial power and node density. We conclude that throughput values are increasing along with the changing of initial power while the delay values are decreasing rapidly. By the changing of node density, the highest delay value is 0.122 ns on 10 nodes condition and 0.215 Mbps for throughput value on 8 nodes condition.